Construction of a genetic decomposition: theoretical analysis of the concept of differential of a function in several variables - Suárez-Aguilar, Zagalo Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper presents a model of the epistemology and cognition, a genetic decomposition (DG), of the concept of differential of a function in several variables (DFSV) of the advanced mathematical thinking (AMT), in terms of mental structures of Action, Process, Object and Schema (APOS) and of the mechanisms for building these structures by reflective abstraction. The DG becomes a reference for the design of teaching strategies and as tool to account for the observable behavior of the subject in understanding the concept.